2018
DOI: 10.5216/rpt.v46i4.51013
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Human Toxoplasmosis in Northeastern Brazil

Abstract: Toxoplasmosis is one of the most prevalent parasitic infections in humans, causing severe clinical complications in immunocompromised patients or in foetuses. Estimates on the toxoplasmosis seroprevalence in human populations vary widely, even within the same region. This study aimed to estimate the prevalence of Toxoplasma gondii infection in the municipality of Santa Cruz, State of Rio Grande do Norte, Brazil, and identify the risk factors for toxoplasmosis. T. gondii IgG antibodies were measured in 66.2% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The univariate analysis showed a significant association between increasing age and seropositivity for T. gondii. This result corroborates with other studies, which found that increasing positivity is directly related to age, probably because older individuals have a greater chance of contact with the agent than do younger individuals (Ybañez et al, 2019;Chacín-Bonilla et al, 2003;Carmo et al, 2010;Gebremedhin et al, 2013;Aloise et al, 2018), but the rate of 6/8 T. gondii in human from F. de Noronha Island infection with age can also vary according to the environment and socioeconomic level (Bahia-Oliveira et al, 2003;Mareze et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The univariate analysis showed a significant association between increasing age and seropositivity for T. gondii. This result corroborates with other studies, which found that increasing positivity is directly related to age, probably because older individuals have a greater chance of contact with the agent than do younger individuals (Ybañez et al, 2019;Chacín-Bonilla et al, 2003;Carmo et al, 2010;Gebremedhin et al, 2013;Aloise et al, 2018), but the rate of 6/8 T. gondii in human from F. de Noronha Island infection with age can also vary according to the environment and socioeconomic level (Bahia-Oliveira et al, 2003;Mareze et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…With respect to schooling, a higher prevalence of infection was observed in individuals with elementary schooling (68.5%). Previous studies have reported that the higher the schooling, the higher the information on preventive care for toxoplasmosis that reduces the risk of infection (Mareze et al, 2019;Aloise et al, 2018;Inagaki et al, 2014;Avelar et al, 2017Avelar et al, , 2018, which reiterates the importance of education and health promotion to prevention of this disease.…”
Section: Discussionmentioning
confidence: 89%
“…The individuals with older age were more likely infected, regardless of gender. These findings corroborate previous reports, which claim that this infection affects 50%‐70% of the Latin‐American adult population and reflects a higher chance of exposure to the parasite with increasing age . The primary source of infection in Brazil is probably caused by the ingestion of oocyst‐contaminated water …”
Section: Discussionsupporting
confidence: 90%
“…These findings corroborate previous reports, which claim that this infection affects 50%-70% of the Latin-American adult population and reflects a higher chance of exposure to the parasite with increasing age. 20,[22][23][24][25] The primary source of infection in Brazil is probably caused by the ingestion of oocyst-contaminated water. 26 Our results have shown a negative association between T gondii infection and atopy (sIgE alone) by analysing the humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%